Implementasi Algoritma K-Means dan Knearest Neighbors (KNN) Untuk Identifikasi Penyakit Tuberkulosis Pada Paru-Paru - Rachmadhany Iman; Basuki Rahmat; Achmad Junaidi (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
In Indonesia, tuberculosis is ranked third in terms of prevalence among countries with the highest tuberculosis burden. Radiological examination, such as X-rays or X-rays, is a method generally used to detect tuberculosis. Chest X-ray examination is one method used to detect tuberculosis. To achieve these goals, the research will combine two powerful data processing techniques. First, the K-Means algorithm will be used to group x-ray image data based on similar characteristics, making it easier to identify typical patterns from images infected with tuberculosis. The research results show the highest accuracy of 93% using data division with a ratio of 80 : 20 with parameter K = 1. These results show that the combined model of the two algorithms can be applied to identify tuberculosis in the lungs.